Seleksi Pemimpin High Potential Talent Dengan Strategi Parenting Program - Albertus Prajartoro (KILAT, 2020)
PT PLN (Persero) has the potential of lacking leaders at the Top Managers and Middle Managers level in the next 10 years. It caused by a very rapid organizational development and delay in the regeneration due to zero growth in 1996-2001 and the existing programs have not been able to meet the needs. To anticipate this, Parenting Program is proposed to be a mentoring and counseling program for High Potential (HiPO) Talen to become a future PLN’s leader with good character and excellent performance. This Program is applied by selecting employees who are in the HiPO criteria and constructed through the parenting program. This study resulted in the determination of Hipo Talent criteria and the criteria of the parent, as well as the proposed program in the form of flow chart and roadmap implementation, and program materials.